Internacionalizando a rede federal de educação profissional: um estudo substantivo. - Souza, Claudia Schiedeck Soares de (Universidade do Vale do Rio dos Sinos, 2019)
The Brazilian Federal Network of Vocational Education was created in 2008 to offer free education to the regions of the country that had no access to higher education and technical education. In 2011, the Ministry of Education instituted the Science Without Borders Program, establishing new challenges for the Federal Institutes. The international context has been marked in recent decades by the rapid growth of Higher Education, perceived by the middle class as a reasonable possibility of social mobility. The main goal of this research is to analyze if there was a model for the internationalization of the Federal Institutes. Specific objectives were to analyze the dynamics of the process, including central and peripheral actors, convergences and divergences in the managers' perceptions, the assumptions that mark the internationalization in the institutions, as well as to delimit what past and present actions may have influenced it and future strategies. The lack of research on the subject pointed to the Situational Analysis, unfolding of the Grounded Theory, as a methodological tool to be used in the study. For data collection, fourteen semi-structured interviews were done, and the interviewed were somehow linked to the beginning of the constitution of the Federal Institutes and their first international activities. The results point to the relevance of these first international experiences of these institutions, notably the Thousand Women Program and the Science without Borders Program, as references in the construction of their internationalization policy. Besides, strategies, multiple partners, and educational cooperation agreements, prioritizing mobility, signal the development of a classic model of internationalization. The distinctive features of this process emerge from the interviewees' speeches and constitute a unique identity for these institutions, based on diversity, resilience, and opportunity. These characteristics are directly related to the perception that the Federal Institutes are associating themselves with their international partners through cooperation, sharing of experiences, institutional respect, learning from, and teaching to them.
Keywords: Educação Profissional; Institutos Federais; Internacionalização; Análise Situacional; Professional Education; Federal Institutes; Internationalization; Situational Analysis; ACCNPQ::Ciências Humanas::Educação